THE CHARACTER VALUES IN TAHFIDZ PROGRAM AT SMP IT AL-FAHMI PALU - Farhan; Askar; Arief, Arifuddin (Al-Tawjih: Jurnal Pendidikan Islam, 2025)
This study aims to describe the implementation of tahfidz program and identify the character values through the program at SMP IT Al-Fahmi Palu. It used a qualitative descriptive approach with observation, interviews, and documentation. The Data was analysed through reduction data, presentation, and verification, while the validity of the data was obtained through source triangulation. The results showed that the Tahfidz programme at SMP IT Al-Fahmi Palu was run systematically and well organized, it covered objectives, schedules, learning methods, teacher competencies, and tahfidz evaluation system. The tahfidz program used IWR (Ilman Wa Ruhan) method, which combined intellectual and spiritual approaches, and it was implemented daily through muroja’ah activities, memorization assignments, and periodic evaluations. This program contributes significantly to shaping the character values of students, including religiosity, discipline, responsibility, honesty, hard work and consistency, independence and confidence, and love for the Qur’an. This study confirmed that the tahfidz programme is important to maintain and develop as a means of shaping the Qur’anic character of students.